2020
DOI: 10.9758/cpn.2020.18.2.231
|View full text |Cite
|
Sign up to set email alerts
|

ZNF804A Gene Variants Have a Cross-diagnostic Influence on Psychosis and Treatment Improvement in Mood Disorders

Abstract: Objective: Genetic variations in the gene encoding zinc finger protein 804A gene (ZNF804A) have been associated with major depression and bipolar disorder. In this work we focused on the potential influence of ZNF804A variations on the risk of developing specific sub-phenotypes as well as the individual response to available treatments. Methods: We used two samples of different ethnic origin: a Korean sample, composed by 242 patients diagnosed with major depression and 132 patients diagnosed with bipolar disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Several of the novel genes identified have evidence in existing literature to be associated with BD and other neuropsychiatric processes ( Table 2 ). For example, ZNF280D , a protein-coding gene, is closely related to its family member ZNF804A , which has been identified as an important factor in bipolar disorder development 35 ; SULT1A3 , another protein-coding gene, has negative effects on sulfation and the impaired sulfation has been proved to have associations with many neurological diseases, such as bipolar disease 36 . Since such gene-based results primarily identify genetic loci, where multiple highly correlated genes can reside, we additionally clumped (See Supplementary for details) the associations based on genomic positions to identify the unique loci or genomic regions identified by each test.…”
Section: Resultsmentioning
confidence: 99%
“…Several of the novel genes identified have evidence in existing literature to be associated with BD and other neuropsychiatric processes ( Table 2 ). For example, ZNF280D , a protein-coding gene, is closely related to its family member ZNF804A , which has been identified as an important factor in bipolar disorder development 35 ; SULT1A3 , another protein-coding gene, has negative effects on sulfation and the impaired sulfation has been proved to have associations with many neurological diseases, such as bipolar disease 36 . Since such gene-based results primarily identify genetic loci, where multiple highly correlated genes can reside, we additionally clumped (See Supplementary for details) the associations based on genomic positions to identify the unique loci or genomic regions identified by each test.…”
Section: Resultsmentioning
confidence: 99%
“…ZNF804A rs1344706 is an intronic SNP which is associated with various psychiatric disorders, especially those characterised by psychosis, and affects depressive symptom improvement in BD after treatment (Calabrò et al, 2020). Zinc finger protein 804A is encoded in humans by the ZNF804A gene that maps to chromosome 2 q32.1; it consists of four exons coding for a 137 kDa protein, whose function is unknown, but its rs1344706 SNP was found to be related to diminished episodic and working memory in patients with schizophrenia (Walters et al, 2010) and to be associated with the self-rated paranoia/ self-reference schizotypal trait (Stefanis et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, for the ZNF804a site rs1344706, it has been revealed that the GG homozygote of the ZNF804a site rs1344706 was related to the increased risk of early onset of SZ. It has also been suggested that the mutation of rs1344706 in ZNF804a gene may affect the cognitive function of SZ patients (32). There is also research revealing that ZNF804a site rs1344706 has no significant effects on the cognitive ability of SZ patients.…”
Section: Introductionmentioning
confidence: 99%